Measuring Parental Behavior towards Children's Use of Media and Screen-Devices: The Development and Psychometrical Properties of a Media Parenting Scale for Parents of School-Aged Children - Lukavská, Kateřina; Vacek, Jaroslav; Hrabec, Ondřej; Božík, Michal; Slussareff, Michaela; Píšová, Martina; Kocourek, David; Svobodová, Lucie; Gabrhelík, Roman (International journal of environmental research and public health, 2021)
Children's excessive screen use is associated with health risks such as obesity, sleep problems, attention problems, and others. The effect of parental regulative efforts focused on screen/media use (media parenting) is currently unclear and difficult to examine given the heterogeneity of measuring tools used for its assessment. We aimed to develop an inventory that would enable reliable and valid measurement of media parenting practices (especially active and restrictive mediation) in parents of primary school children. The inventory builds on existing tools, it is comprehensive, yet easy to use in research setting. The original MEPA-36 (36 items) and revised MEPA-20 (20 items) inventories were examined using data from 341 Czech and Slovak parents of children aged between 6 and 10 years. Psychometrical properties were estimated using confirmatory factor and reliability analyses. Model fit was better for MEPA-20 and similar to other currently available tools. Both active and restrictive mediation subscales demonstrated high internal consistency. The internal consistency of newly constructed risky mediation subscales (risky active, risky restrictive, and over-protective mediation) was low. MEPA-20, especially active and restrictive mediation subscales, can be recommended for research on media parenting in context of screen/media use of school-aged children.
Keywords: Psychometrics; media parenting; self-report; Parenting; psychometrics; rodičovství; chování dětí; Child; measurement; screens; dítě; media use; reprodukovatelnost výsledků; průzkumy a dotazníky; Reproducibility of Results; parental mediation; Schools; školy; lidé; restrictive mediation; psychometrie; Humans; active mediation; Child Behavior; Surveys and Questionnaires; vztahy mezi rodiči a dětmi; inventory; Parent-Child Relations